Bioethical issues relating to farmers’ rights arising from genetically modified crops in Malaysia / Siti Hafsyah Idris - Idris, Siti Hafsyah (2012)
Concerns on genetically modified (GM) crops focused on intrinsic ethical concerns on whether it should be permissible to intgrvene in the natural process and also concerns on the principle of playing God and changing the creations of God. Later, bioethical debate on GM crops focused on extrinsic bioethics inclusive ofexplohing the potential benefits ofthis technology and corporate-dominated seed sector. For the purpose ofthis thesis, the discussion focuses on bioethical issues relating to farmers‘ rights arising from GM crops‘ Bioethical issues on farmers‘ rights include the struggle of the farmers to balance GM crops" benefits and demands, with conventional livelihood viability, and seek to preserve their autonomy‘ Bioethical issues to farmers‘ rights also concern ‘he right of farmers who have little control over contractual decisions leading to unfair justice‘ Previous research in Malaysia has not addressed these issues. This research is pertinent because it would provide the investigation ofthe existing biosafety regulatory measures in protecting farmers’ rights arising from GM crops and to revise any gaps in the regulatory measures, This thesis examines the bioethica] issues relating to farmers‘ rights in ‘he biosafety regulatory measures ofGM crops: the comprehensiveness ofthc biosafety regulatory measures in protecting bioethical issues affecting farmers' rights in Malaysia arising in GM crops as compared to other countries such as India and Australia, focusing on the farmers‘ rights to livelihood: and farmers‘ rights to comractual obligations; and suggests the biosafety regulatory measures to address the protection of bioethical issues pertaining to farmers‘ rights arising from GM crops, [n this research, doctrinal and empirical methods have been combined. While the doctrinal method is a research of legal preposition by way of analysing the exi' ing statutory provision along with the present case laws to find out gap, the emp a] research empluys methods through semi-structured interviews to generate empirical data that answers research questions. The research found that the protection ofbioe‘hical issues relating to fanners‘ rights arising from GM crops is significant to be addressed in the biosafety regulatory measures to ensure their rights as one of the stakeholders in this technology are protected agains‘ the rapid revolutionary scientific assessment of this :echnology. The research also found that the current biosafety regulatory measures. which conforms to the Precautionary Principle as the guiding principle, are incomprehensive to address bioethical issues relating to farmers' rights arising from GM crops: hence, protection needs to be strengthened through the ethical approach. namely Principlism to further enhance the comprehensiveness of ‘he Precautionary Principle. Finally, the recommendations proposed based on experiences from differences in jurisdictions and empirical data method to further enhance the comprehensiveness oflhe biosafety regulatory measures in protecting bioethical issues relating to farmers‘ rights. This study will n01 only contribute to the understanding of the relevant laws surrounding the bioethical issues relating to farmers‘ rights on GM crops based on the current Precautionary Principle approach but also, to propose a better approach, which is Principlism m further enhance the existing Precautionary Principle and therefore regulating this area for the betterment offarmers‘ rights.